Experimental investigations and computer modeling of the photochemical processes in Ag-As₂S₃ structures using surface plasmon resonance spectroscopy - Chegel’, V.I.; Shirshov, Yu.M.; Kostyukevich, S.O.; Shepeliavy, P.E.; Chegel', Yu.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Surface plasmon resonance (SPR) was first applied for investigation of the initial stage kinetics of the chemical processes in inorganic resist based on thin-film Ag-As₂S₃ structure. This method enabled to measure optical constants for the super-thin layers (from 0.2 up to 50 nm) and to study the changes in structure and thickness of the films after their exposure with different doses of UV radiation. Computer matching of the experimentally obtained SPR curves enabled to justify the assumption concerning the presence of a thin (close to 0.7-1 nm) intermediate layer with the parameters similar to Ag₂S, which is created during formation of the Ag-As₂S₃ structure, and also estimate its evolution in the course of layers interaction.